Antioxidant properties in callus cultures and intact plant parts of Gynura procumbens (Lour.) - Krishnan, Vijendren (2014)
Gynura procumbens (Lour.) Merr. which is locally known as sambung nyawa hijau in Malaysia is a beneficial plant known to pose anti-diabetic, anti-hypertensive. antiinflammatory and anti-hyperlipidaemic effect. Gvnura bicolor (Roxb. Ex Willd.)OC. another species of Gynura bicolor that is available locally also known as sam bung nyawa merah has been used traditionally for medicinal purposes. Due to the fact that no reports on the tissue culture protocols and quantitative analyses on antioxidative properties of G. procumbens, this research were undertaken to optimize ill vitro culture for G. procunibens leaf, stem and root derived callus and to investigate the antioxidunt properties of G. procumbens and G. bicolor. The effect of auxins on the callus induction was investigated and followed by the investigation of callus proliferation using various auxins singly and also in combination with cytokinins. Callus growth rate was also investigated on the optimized medium. In addition. antioxidant properties of G. procumbens intact parts and its leaf, stem and root derived callus were investigated in comparison to the intact parts from G. bicolor by means of OPPH radical scavenging assay, ferric reducing antioxidant power, total phenolic content, total flavonoid content and ascorbic acid determination. Callus initiation was achieved by culturing intact plants on full-strength Murashige and Skoog medium augmented with 2,4-0, Die, NAA and Pic. The stem induced its earliest callus after five days of culture, while root explant induced callus only after IS days of culture on NAA treatment. Leaf callus was initiated earliest after seven days of culture on Pic treatment. Investigation on callus propagation conducted on various concentration of auxins viz. 2,4-0, Die, IAA. IBA, NAA and Pic, revealed the highest callus dry biomass in medium augmented with 10 11M2,4-0 for leaf and root callus while IS 11M 2,4-0 for stem callus. Hence, further investigation was carried out in media supplemented with combination of 2,4-0 and various cytokinin which resulted in highest biomass on 10 11M 2.4-0 and 7.5 11M BAP (0.269 ± 0.010 g OW) for leaf callus. 15 ~IM 2,4-0 and 7.5 ~IM BAP (0.246 ± 0.012 g OW) for stem derived callus and 10 11M2.4-0 and 5.0 11MBAP (0.254 ± 0.010 g OW) for root derived callus. Meanwhile, studies on antioxidative properties revealed that G. procunibens root explant possessed the highest antioxidant activity among all explants in all the antioxidant assays conducted.